Pengaruh Komunikasi Visual Desain Grafis Buku Mizan Terhadap Minat Baca Anak - Ummy Chairiyah; Fandi Achmad (Jurnal Ilmu Komunikasi, 2022)
Children's books that use graphic design are currently in great demand by children. Mizan Publisher has published a book that utilizes the concept of graphic design as a way to attract children's reading interest. Graphic design elements in children's books are the key to successful persuasion.This study aims to measure the extent to which graphic design as a propaganda medium affects reading interest. The research uses a quantitative method through parametric statistics with a Likert scale. The correlation analysis is examined by using simple linear regression analysis, Pearson correlation test,  and coefficient of determination test. Based on the simple regression test the result has revealed that the value of r = 0.767 and has a coefficient of determination of 17.7%. Which shows that there is a positive and very strong relationship between the influence of visual communication on graphic design of Mizan's book on reading interest by 17.7%.